ANALISIS HUKUM PADA KEBIJAKAN PEMBEBASAN TANAH UNTUK KEPENTINGAN UMUM DI INDONESIA - Tine Suartina (Jurnal Masyarakat dan Budaya, 2008)
Land acquisition for public purpose in Indonesia is a crucial matter since it relates with people’s land ownership and livelihood. In Indonesia, the problems are divided in two: laws and regulations; and its practice or implementation. Through legal analysis and interpretation method, this article will focus on observing weaknesses in the law and regulations concerning land acquisition for public purpose in Indonesia – aside from the practical observation-, whereas laws and regulations are important tools in the policy implementation but are potential to be used for any intention different with public interest. The setting of land acquisition for public purpose policy in Indonesia, including in the laws and regulations, contains many problems and weaknesses, such as unstable definition of ‘public interest’ as the reason of land acquisition and expropriation; possibility for private sector involvement – which is actually forbidden based on the concept taken from Constitution Article 33 (1) and State Controlling Rights-; influence and intervention from international and donor institutions in transplanting their policies which sometimes not always in the line with domestic policy. However, without neglecting the review on its weaknesses, positive aspects can be found in the compensation arrangement which has some benefits for land owners. Legal analysis on laws and regulations related is carried out to explain those weaknesses and positive aspects. Particularly, the controversial Presidential Regulation 36/2005 stipulation case is an important example in understanding land acquisition for public purpose policy problems in Indonesia.